Utilization of ornamental rock waste as a catalytic support for α-MoO₃ in biodiesel production - H. B. Sales; M. S. Oliveira; A. L. Silva; H. L. Pereira; A. C. F. M. Costa; M. C. F. Alves (Scientific Reports)
Abstract This study aimed to explore the use of ornamental stone waste as a support for the α-MoO₃ catalyst to develop efficient and sustainable heterogeneous systems for biodiesel production. The catalysts were characterized using physicochemical techniques including X-ray diffraction with Rietveld refinement, FTIR and Raman spectroscopy, scanning electron microscopy with EDS, transmission electron microscopy, nitrogen adsorption/desorption (BET method), particle size distribution, ammonia temperature-programmed desorption (TPD-NH₃), magnetic measurements, and gas chromatography to analyze simultaneous transesterification/esterification (TES) reactions and quantify methyl and ethyl esters. XRD patterns revealed crystalline phases such as mica-biotite, ferro-tschermakite, albite, quartz, and iron-magnesium silicates—components of the catalytic support—as well as orthorhombic α-MoO₃ phases, also confirmed in the heterogeneous systems. FTIR and Raman analyses showed characteristic vibrational bands, while SEM images displayed irregular agglomerates, corroborated by TEM. Nitrogen adsorption isotherms indicated mesoporous structures with surface areas ranging from 0.615 to 3.87 m²/g. Particle size analysis showed D₅₀ values between 5.02 and 20.00 μm, with total acidity ranging from 77.0 to 245 µmol/g of NH₃. Magnetic tests indicated ferrimagnetic behavior. The catalytic performance confirmed the effectiveness of the waste as a support for α-MoO₃, particularly in the system containing 40% Mo ions (40%σ-MoO₃:Waste), which achieved conversions between 78% and 95%. These findings highlight the environmental and technological potential of the studied catalysts, reinforcing the economic viability and ecological relevance of reusing industrial waste in the sustainable production of biodiesel from waste oils.